Reconstruction with interference screw of ruptured distal biceps brachii tendon at level of insertion into radial tuberosity: a case report - Stanu, Gusti Ngurah Putra; Wien Aryana, I. Gusti Ngurah; Purvance, Ivander; Dewi Astawa, Ni Made Puspa (International Journal of Research in Medical Sciences, 2020)
Distal biceps tendon rupture is a relatively rare injury. The incidence of distal biceps rupture is 1.2 cases per 100,000 patients per year, with the average age is 47 years old and the majority is male patient with dominant extremity. A 43 years old male presented with pain of the left elbow and weakness to flex and supinate the forearm following gymnastic activity. He heard pop sound on his left elbow during lifting dumbbell and followed by a sudden pain on his arm and weakness to flex and supinate the elbow. The USG examination were performed and confirmed there was a rupture on the distal biceps tendon at the level of insertion. Durante operation confirmed a complete rupture of distal biceps tendon. A Henry approach incision is performed to expose radial tuberosity, and the ruptured tendon was reconstructed by anchored into the tuberosity of radius with bioabsorbable screw. After closing the incision, patient is immobilized by cast in 60 to 90o elbow flexion and neutral pronosupination. Distal biceps tendon rupture can be successfully repaired by single anterior approach using anatomical anchor on radial tuberosity, so that can avoid posterior approach and associated proximal radioulnar synostosis risk while conserving interosseous membrane.